Low-cost Machine Vision System for dimension measurement of fast moving conveyor products - Arsalan, M.; Aziz, A. (2012 International Conference on Open Source Systems and Technologies, 2012)
Product manufacturing industries growth and efficiency greatly depends upon the quality of end product. Hence, it is necessary to inspect each and every object for its quality during manufacturing process. Machine Vision system can be implies here for indispensable advantages. Commercial Vision systems available in market are very expensive. Industries especially in third world countries like Pakistan it is not easy for them to utilize Typical Machine Vision System in place of conventional measuring methods due to economic reasons. Keeping this scenario in mind, an attempt was made to develop a Low-Cost Machine Vision System. The paper presents a design of Machine Vision System capable of object monitoring with the resolution up to 0.3mm. Real time Image processing of moving conveyor objects has performed. Different measurement inspection procedures have been performed including length measurement, diameter measurement and object feature counting. Practical Project Testing gives out measurement results up to 99% accuracy.